Developing primary mathematics teaching : reflecting on practice with the knowledge quartet - Rowland, Tim, 1945- (Los Angeles : SAGE, 2009)
This title helps readers to become better, more confident teachers of mathematics by enabling them to focus critically on what they know and what they do in the classroom. Each chapter includes practical activities, lesson descriptions and extracts of classroom transcripts to help teachers reflect on effective practice.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain; Electronic books